A QUEST FOR GROWTH IN COST PRODUCTIVITY OF AGRICULTURE SECTOR - Dr. Majid Ali, Dr Shahzad Mushtaq, Dr. Muhammad Abdullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Punjab’s key natural resources are arable land and water which makes it major contributor to the total agriculture production of the national economy. This contribution can be enhanced further by increasing productivity of this sector. For enhancing the productivity, it is necessary to know the existing level and determinants of Productivity. Keeping in view this fact, present study is an effort estimate and decompose the input-oriented cost Malmquist productivity index agriculture sector of Punjab, Pakistan. District-wise data of Punjab province has been used from 2012-13 to 2014-15. The cost Malmquist indices have been computed by applying the data envelopment analysis. The results indicate that the cost productivity increased by 24.56% and the technical productivity grew by 2.6% during 2012–2015. The increase in the total factor productivity was mainly driven by growth in technological innovation. Therefore, it may be concluded that the impact of efficiency on the overall shifts in the production frontier was very scanty.